State of the art in anaerobic treatment of landfill leachate: a review on integrated system, additive substances, and machine learning application - Zamrisham, Nur Ain Fitriah; Abdul Wahab, Abdul Malek; Zainal, Afifi; Karadag, Dogan; Bhutada, Dinesh; Suhartini, Sri; Musa, Mohamed Ali; Idrus, Syazwani (Multidisciplinary Digital Publishing Institute, 2023)
Leachates from landfills are highly polluted with a considerable content of organic and inorganic pollutants which pose severe deterioration to environment including soil, groundwater, surface water and air. Several mitigative measures have been applied for effective management of leachate such as biological treatment, engineering device control leachate migration, physical/chemical treatment, and membrane technology. Among the alternatives, anaerobic digestion (AD) is promising, with effective removal of pollutants and high potential for renewable energy production and nutrient recovery. Landfill leachate (LFL) is an excellent source as a substrate in an AD system, with its high content of organic matters. The advantages and disadvantages of AD of LFL were extensively discussed in this review in terms of its potential as a co-substrate, pre-treatment application, and the types and design parameters of the digester. The review critically evaluated the previous studies on leachate treatment using an AD system as well as potential factors which can enhance the treatment efficiency, including the application of an integrated system, additive substances as well as potential inhibition factors. Pre-treatment methods have the potential to meet desired effluent quality of LFL before discharging into receiving bodies. The review also highlighted the application of kinetic modelling and machine learning practices, along with the potential of energy generation in AD of LFL. Additionally, the review explored the various strategies, and recent advances in the anaerobic treatment of LFL, which suggested that there is a requirement to further improve the system, configuration and functioning as a precursor in selecting suitable integrated LFL-treatment technology.